EXPLORING THE AMENABILITY OF ONIONS TO AGROBACTERIUM MEDIATED TRANSFORMATION - K. Amin; A. Bakhsh; A. F. Gökçe (Journal of Animal and Plant Sciences, 2019)
The onions exhibit recalcitrant nature when subjected to genetic modifications. The study was conducted to optimize various factors affecting Agrobacterium mediated transformation in onion. Factors such as genotype dependency, type of explants and response of growth regulators were investigated. Agrobacterium strain LBA4404 harboring pBIN19 binary vector was used to infect different explants of two cultivars (Kral and Sampiyon). The T-DNA region of vector contained uidA gene (interrupted by an intronic sequence) to screen primary transgenic shoots at earlier stage and nptII gene as plant selectable marker. Results exhibited the genotype and explant dependency towards genetic modification of both cultivars. Based on the rate of callus induction, regeneration response and GUS histochemical assays, cultivar “Kral” was found better compared to “Sampiyon”. The best callus induction was observed on MS medium supplemented with 1:10 ratio of 2,4-D and BAP respectively. Out of 355 primary transformants, 87 primary transformants were recorded as positive when subjected to PCR assays; 51 belonging to Kral showing tendency of genotype to genetic improvement. Results showed that highest number of putative transgenic plants was contributed by mature embryos followed by seeds and basal plates explants. Onion seed as explant has been used successfully for first time as no evidence in earlier literature was found. The optimization of these factors in Agrobacterium tumefaciens-mediated transformation will provide a gateway to introduce any desired trait in onion.
Keywords: Genetic transformation; onion; regeneration; GUS analysis; transgenes